Method for improving whiteness of nano calcium carbonate
By adding whitening converter and crystallization regulator in the process of carbonization of nano calcium carbonate, and using a liquid film reactor for coating and crystallization, the problems of complex and low efficiency of whiteness enhancement methods in the prior art are solved, and high The preparation of whiteness nano calcium carbonate has the advantages of environmental protection, safety and high added value.
Patent Information
- Application Number
- CN202411479616.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art whiteness enhancement method in the preparation process of nano calcium carbonate is complex and inefficient, and there are limitations on ore grade and impurity types, making it difficult to meet the market demand for high-whiteness products.
During the carbonization process of nano calcium carbonate, whitening converter and crystallization regulator are added, and the coating and crystallization are strengthened through the liquid film reactor. Combining the preferential treatment of dilute carbon dioxide and dilute calcium bicarbonate solution, high-whiteness nano calcium carbonate can be achieved. preparation.
It significantly improves the whiteness of nano calcium carbonate, has a simple process and is environmentally friendly, avoids the use of hazardous chemicals, reduces process costs, has high added value for products, and has wide applicability.
Smart Images

Figure CN119306241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic powder surface modification, and in particular to a method for improving the whiteness of nano calcium carbonate powder. Background Art
[0002] my country is a big country in the production and demand of nano calcium carbonate, but precipitated calcium carbonate with certain technical added value only accounts for 10% of the product structure, and nano calcium carbonate with high added value accounts for less than 1% of the total output; at the same time, the dispersion and performance stability of nano calcium carbonate products are poor, far from meeting the market demand, and more than 100,000 tons must be imported every year. In addition, with the development of the national economy and the improvement of people's living standards, the demand for light-colored products is increasing, but my country has abundant reserves of low-grade limestone, while high-quality high-whiteness limestone is scarce, especially the limestone formed in the Cambrian period, which has low taste, black color, high content of impurities such as silicon, magnesium, and iron, and cannot meet the market's whiteness requirements for inorganic powder materials; on the other hand, with the increasing demand for high-whiteness nano calcium carbonate in my country's papermaking, toothpaste and other industries, the whiteness of nano calcium carbonate in the market is mostly 90%, the output of high-whiteness nano calcium carbonate is low, and the supply and demand are unbalanced. Therefore, improving the whiteness of nano calcium carbonate powder has become one of the important indicators for the refinement of nano calcium carbonate production.
[0003] At present, there are physical and chemical methods for whitening in the preparation process of nano calcium carbonate. Common physical methods are divided into mechanical crushing, hand selection, gravity separation and magnetic separation and iron removal. The mechanical crushing method is to obtain impurity monomers by crushing the raw materials, and then remove impurities through multiple steps such as manual sorting and color sorting machine sorting. The process is complicated and the whitening effect is poor. The hand selection method requires the naked eye to observe the differences in ore color and density, which is inefficient and time-consuming. The gravity separation method removes impurities based on the principle of mineral density difference, and can only guarantee the whiteness and purity of the raw materials to a certain extent. The magnetic separation and iron removal method uses electromagnetic force to capture magnetic impurities through the magnetic differences of various substances. This method has high sorting efficiency and strong processing capacity, but it is only suitable for the removal of magnetic substances. At the same time, it is difficult to achieve magnetic separation for limestone, which is very easy to break.
[0004] Hu Qingfu et al. pointed out in the study of chemical whitening technology of light calcium carbonate (Inorganic Salt Industry, 2008, 40(2), 38-40.) that chemical whitening methods mainly include oxidation-reduction method, chemical coating method and dissolution pretreatment method. The oxidation-reduction method uses a strong reducing agent to convert Fe 3+ and its oxides are reduced to Fe 2+, with complexing agent and pH regulator to filter and remove Fe impurities in production, but the added strong reducing agent is prone to side reactions, which will not only cause excessive consumption of the agent, but also affect the product quality. In addition, if the product is not washed and dried in time, it will cause the product to turn yellow. The chemical coating method includes mechanical coating method and chemical precipitation method. Among them, the chemical precipitation method has a tighter combination due to the chemical reaction, and the whitening effect is better. CN200610048062 discloses a method of using mechanical coating and chemical coating to eliminate brucite powder chromophore impurities to improve whiteness, but this method needs to go through a complex mechanical treatment process, cannot achieve in-situ modification and has a complex process. The dissolution pretreatment process is mainly used to prepare CaCO3 from carbide slag. In the study on preparing high-whiteness plate-like calcium carbonate from carbide slag (Journal of Xi'an Jiaotong University, 2004, 39(9), 989-990.), Lu Zhongyuan and his team used NH4Cl to dissolve carbide slag, controlled the pH to separate oxide impurities such as Si, Fe, Al and Mg, and then introduced CO2 to carbonize and obtain CaCO3 powder. The process is complicated and the conditions are difficult to control.
[0005] In view of this, it is urgent to develop a nano-calcium carbonate whitening method with simple process, wide applicability, environmental friendliness and high efficiency. Summary of the invention
[0006] The present invention solves the problems existing in the prior art and provides a method for improving the whiteness of a product during the preparation of nano calcium carbonate. The whiteness of the powder is improved by adding a whitening conversion agent during the carbonization process of nano calcium carbonate. The present invention significantly reduces the limitation of impurities in ore raw materials, especially the limitation of iron content, improves the added value of nano calcium carbonate products, and has the advantages of being environmentally friendly and free of hazardous chemicals.
[0007] In order to achieve the above-mentioned object, the present invention provides a method for improving the whiteness of nano-calcium carbonate powder. The technical feature of the method is that a whitening conversion agent and a crystallization regulator are added to the calcium hydroxide slurry at the end of the carbonization stage of producing nano-calcium carbonate to coat and crystallize the nano-calcium carbonate, and then nano-calcium carbonate with higher whiteness is obtained through separation.
[0008] In order to better achieve the effect of the present invention, the present invention also adopts the following combined strategies in the specific implementation process, including the effective regulation of the concentration of the calcium hydroxide slurry and the end of carbonization of the present invention, the whitening conversion agent is a mixture of MgSO4, Mg(NO3)2, MgCl2, MgAc2, Mg(HCO2)2 and the corresponding calcium zinc barium mixed salt selection, oleic acid, stearic acid, citric acid, EDTA, isopropanol, benzoic acid and other crystallization regulators regulation, and the liquid film reactor to strengthen the coating process, and at the end of carbonization using dilute carbon dioxide and dilute calcium bicarbonate solution carbonizing agent is preferred, thereby organically forming a method for improving the whiteness of nano calcium carbonate.
[0009] Compared with the prior art, the present invention has the following advantages:
[0010] 1. The present invention is not limited by the ore grade and impurity types and has wide applicability.
[0011] 2. In the process of preparing nano calcium carbonate, the whitening conversion agent is directly added to prepare the whitening integrated product, which has a simple process flow and is environmentally friendly.
[0012] 3. Compared with the chemical whitening method, the present invention has simple chemical reagents, does not involve hazardous chemicals, and has a high safety production coefficient.
[0013] 4. The process cost is relatively low and the product added value is high. The high whiteness nano calcium carbonate produced has strong competitiveness and good product benefits. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0015] 1. A method for improving the whiteness of nano calcium carbonate, characterized in that a whitening conversion agent and a crystallization regulator are added to a calcium hydroxide slurry at the end of the carbonization process of producing nano calcium carbonate, and the surface of the nano calcium carbonate is subjected to a strengthening coating and crystallization process in a liquid film reactor to obtain high-whiteness nano calcium carbonate through separation.
[0016] 2. the calcium hydroxide slurry in the method as claimed in claim 1, is characterized in that calcium hydroxide concentration is 4-12%, preferably 6.5-9.0%.
[0017] 3. The carbonization end stage as claimed in claim 1 is that the carbonization rate of the calcium hydroxide slurry reaches 75-98%, preferably 85-96%.
[0018] 4. The whitening conversion agent as described in claim 1 is a mixture of MgSO4, Mg(NO3)2, MgCl2, MgAc2, Mg(HCO2)2 and corresponding calcium zinc barium mixed salts, Mg:CaZnBa=1-12:1, preferably 1.5-6.0:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:(0.02-0.6):(0.03-0.5), preferably 1:(0.03-0.2):(0.05-0.2).
[0019] 5. The crystallization modifier as claimed in claim 1 is oleic acid, stearic acid, citric acid, EDTA, isopropanol, benzoic acid, and the weight percentage concentration of the crystallization agent is 0.1-4.5%, preferably 0.5-1.5%.
[0020] 6. The coating process in the method as claimed in claim 1 is an enhanced coating process carried out in a super liquid membrane reactor, wherein the slit is controlled to be 0.3-2.0 μm, preferably 0.5-1.0 μm, and the number of treatments is controlled to be 1-10 times, preferably 3-5 times.
[0021] 7. the crystallization process in the method as claimed in claim 1 is that the nano-calcium carbonate slurry after the coating process of liquid film reactor carries out freezing and aging process, wherein the nano-calcium carbonate slurry is cooled to 0-35 ℃, preferably 5-20 degrees Celsius, and the aging process keeps constant temperature stirring 2-180min, preferably 5-30min, and stirring speed 150-3000 rev / min, preferably 300-900 rev / min.
[0022] 8. The whitening conversion agent as described in claims 1, 3, and 4 accounts for 0.3-6% by weight of the nano-calcium carbonate, preferably 0.6-3.2% by weight.
[0023] 9. The conversion process of the whitening conversion agent as described in claims 1, 3, 4 and 8 is a hydroxide precipitation and carbonate precipitation process occurring between pH values of 6.5-13.5, wherein the preferred pH is 7.5-10.5.
[0024] 10. The carbonizing agent in the carbonization final stage of the method as claimed in claims 1, 2 and 3 is dilute carbon dioxide and dilute calcium bicarbonate solution, wherein the carbon dioxide weight percentage concentration is 3-40%, preferably 5-21%, and the dilute calcium bicarbonate concentration is 1-7%, preferably 3-5%.
[0025] The present invention is described in detail below through examples, but the protection scope of the present invention is not limited to the contents described above.
[0026] The following examples all use limestone provided by Jidong Cement Panshi Co., Ltd. as raw material. After analysis, the impurity composition and content in the Panshi limestone are: 1.6% MgCO3, 1.0% SiO2, 0.1% Al2O3, and 0.2% Fe2O3.
[0027] Example 1
[0028] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0029] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, which is equivalent to 93% of the calcium hydroxide being converted into calcium carbonate, and then cooled to 18°C.
[0030] (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 2.5wt% MgCl2 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid passes through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, ventilation is stopped, and constant temperature stirring is maintained for 15 minutes. After the stirring speed is 300rpm, separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0031] Example 2
[0032] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0033] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, and then cooled to 18°C. (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 2.5wt% MgSO4 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid passes through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the constant temperature stirring is maintained for 15 minutes, and the stirring speed is 300rpm, and then separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0034] Example 3
[0035] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0036] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, and then cooled to 18°C. (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 2.5wt% Mg(NO3)2 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid is passed through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the constant temperature stirring is maintained for 15 minutes, and the stirring speed is 300rpm, and then separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0037] Example 4
[0038] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0039] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, and then cooled to 18°C. (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 0.5wt% MgCl2 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid passes through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the constant temperature stirring is maintained for 15 minutes, and the stirring speed is 300rpm, and then separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0040] Example 5
[0041] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0042] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, and then cooled to 18°C. (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 1.0wt% MgCl2 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid passes through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the constant temperature stirring is maintained for 15 minutes, and the stirring speed is 300rpm, and then separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0043] Example 6
[0044] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0045] (2) The calcium hydroxide slurry obtained in (1) is carbonized to 93% with carbon dioxide, and then cooled to 18°C. (3) A kiln gas with a concentration of 20% carbon dioxide is introduced, and 1.5wt% MgCl2 and a calcium zinc barium mixed salt are added, wherein Mg:CaZnBa=5:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:0.05:0.08, and a stearic acid solution with a weight percentage concentration of 1.0% is added. The slit of the super liquid membrane reactor is controlled to be 0.5μm, and the reaction liquid passes through 3 times. (4) When the pH at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the constant temperature stirring is maintained for 15 minutes, and the stirring speed is 300rpm, and then separation is performed to obtain a whitened nano calcium carbonate sample. The product is dried at 110°C to obtain a nano calcium carbonate product, and its whiteness is shown in Table 1.
[0046] Comparative Example 1
[0047] (1) Using Panshi limestone ore as raw material, the limestone is calcined and digested to obtain 8wt% Ca(OH)2;
[0048] (2) The calcium hydroxide slurry obtained in (1) was carbonized to 93% with carbon dioxide and then cooled to 18° C. (3) A carbon dioxide kiln gas with a concentration of 20% was introduced, the slit of the super liquid membrane reactor was controlled to be 0.5 μm, and the reaction liquid was passed through 3 times.
[0049] (4) When the pH value at the end of carbonization is controlled to be 7.6, the ventilation is stopped, and the stirring is maintained at a constant temperature for 15 minutes at a stirring speed of 300 rpm, and then the whitened nano-calcium carbonate sample is obtained by separation. The product is dried at 110°C to obtain a nano-calcium carbonate product, the whiteness of which is shown in Table 1, and the scanning electron microscope (SEM) is shown in Figure 1 .
[0050] It should be understood that parts not elaborated in detail in this specification belong to the prior art.
[0051] It should be understood that the above description of the preferred embodiment is relatively detailed and cannot be regarded as limiting the scope of patent protection of the present invention. Under the enlightenment of the present invention, ordinary technicians in this field can also make substitutions or modifications without departing from the scope of protection of the claims of the present invention, which all fall within the scope of protection of the present invention. The scope of protection requested for the present invention shall be based on the attached claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Table 1 Whiteness values of nano calcium carbonate prepared in specific examples and comparative examples
[0053] Figure 1 Scanning electron microscope image of nano calcium carbonate prepared using Panshi limestone ore as raw material
[0054] Table 1
[0055]
Claims
1. A method for improving the whiteness of nano calcium carbonate, characterized in that After adding a whitening conversion agent and a crystallization regulator to the calcium hydroxide slurry at the end of the carbonization process in the production of nano calcium carbonate, the surface of the nano calcium carbonate is subjected to a strengthening coating and crystallization process in a liquid membrane reactor, and then high-whiteness nano calcium carbonate is obtained through separation.
2. The calcium hydroxide slurry according to the method of claim 1, characterized in that The concentration of calcium hydroxide is 4-12%, preferably 6.5-9.0%.
3. The carbonization end stage as claimed in claim 1 is that the carbonization rate of the calcium hydroxide slurry reaches 75-98%, preferably 85-96%.
4. The whitening conversion agent as described in claim 1 is a mixture of MgSO4, Mg(NO3)2, MgCl2, MgAc2, Mg(HCO2)2 and corresponding calcium zinc barium mixed salts, Mg:CaZnBa=1-12:1, preferably 1.5-6.0:1, and the atomic ratio of the calcium zinc barium mixed salt is 1:(0.02-0.6):(0.03-0.5), preferably 1:(0.03-0.2):(0.05-0.2).
5. The crystallization modifier as claimed in claim 1 is oleic acid, stearic acid, citric acid, EDTA, isopropanol, benzoic acid, and the weight percentage concentration of the crystallization agent is 0.1-4.5%, preferably 0.5-1.5%.
6. The coating process in the method as claimed in claim 1 is an enhanced coating process carried out in a super liquid membrane reactor, wherein the slit is controlled to be 0.3-2.0 μm, preferably 0.5-1.0 μm, and the number of treatments is controlled to be 1-10 times, preferably 3-5 times.
7. the crystallization process in the method as claimed in claim 1 is that the nano-calcium carbonate slurry after the coating process of liquid film reactor carries out freezing and aging process, wherein the nano-calcium carbonate slurry is cooled to 0-35 ℃, preferably 5-20 degrees Celsius, and the aging process keeps constant temperature stirring 2-180min, preferably 5-30min, and stirring speed 150-3000 rev / min, preferably 300-900 rev / min.
8. The whitening conversion agent as described in claims 1, 3, and 4 accounts for 0.3-6% by weight of the nano-calcium carbonate, preferably 0.6-3.2% by weight.
9. The conversion process of the whitening conversion agent as described in claims 1, 3, 4 and 8 is a hydroxide precipitation and carbonate precipitation process occurring between pH values of 6.5-13.5, wherein the preferred pH is 7.5-10.
5.
10. The carbonizing agent in the carbonization final stage of the method as claimed in claims 1, 2 and 3 is dilute carbon dioxide and dilute calcium bicarbonate solution, wherein the carbon dioxide weight percentage concentration is 3-40%, preferably 5-21%, and the dilute calcium bicarbonate concentration is 1-7%, preferably 3-5%.
Citation Information
Patent Citations
Method for removing brucite powder chromophore impurity
CN1970486A